2002
DOI: 10.1002/jbm.10208
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological changes in resin‐dentin bonds after 1 year of water storage

Abstract: The purpose of this study was to evaluate the degradation of resin-dentin bonds after 1 year of water storage. Resin-dentin-bonded specimens were prepared with the use of an adhesive resin system (One-Step: Bisco). Half of the experimental specimens were sectioned perpendicular to the adhesive interface to produce a beam (adhesive area: 0.9 mm(2)) before being stored in distilled water at 37 degrees C for 1 year. The remaining half of the bonded specimens were sectioned into beams of similar dimensions after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
162
1
27

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(195 citation statements)
references
References 11 publications
5
162
1
27
Order By: Relevance
“…[8][9] On the other hand, it has been reported that a comparatively higher bond strength was obtained for self-etching primer adhesive systems with the creation of a submicron resin tag. 10 The question arises whether the resulting bonds might be stable after thermal cycle stressing. 11 With tooth colored restorations, evaluation for bonding durability is important, since stability of the bond between the restoration and tooth substrate is important for long-term clinical success.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9] On the other hand, it has been reported that a comparatively higher bond strength was obtained for self-etching primer adhesive systems with the creation of a submicron resin tag. 10 The question arises whether the resulting bonds might be stable after thermal cycle stressing. 11 With tooth colored restorations, evaluation for bonding durability is important, since stability of the bond between the restoration and tooth substrate is important for long-term clinical success.…”
Section: Introductionmentioning
confidence: 99%
“…However, marginal discoloration or recurrent caries are frequently found in clinical resin restoration for long-term use. Several in vivo [1][2][3][4] and in vitro studies [5][6][7][8] have shown the degradation mechanism of the bonds. However, information on bond degradation is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, information on bond degradation is very limited. Degradation analysis has mainly been conducted with the use of water storage testing [5][6][7][8] or human 2,3 and monkey models. 1,4 However, in these test methods the disadvantage is that a long test span (i.e., months or years) is needed to obtain results.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete infiltration of an adhesive into etched dentin reduces the bond strength as well as the durability of the restoration, because acid-etched exposed collagen fibrils unprotected by resin have been shown to be morphologically altered after long-term storage in water (21). In such a case, storage in water would cause partial demineralization of the surface layer, and this would be detected by the surface sensitive method.…”
Section: Discussionmentioning
confidence: 99%